Systematic review of salted meat and its quality processes (Research, Society and Development, 2021)
This research consists of a systematic review developed based on studies of the origin and evolution processes of salted meat, as well as the quality parameters practiced by the industrial and artisanal sector concerning this product. O Regulamento da Inspeção Industrial e Sanitária de Produtos de Origem Animal (RIISPOA) defines as salted meat any edible product, prepared based on meat or organs, treated with sodium chloride, or by mixing other salts with nitrates, nitrites, spices, and sugars. Therefore, this study aims to rescue, through a systematic review, the literature, history, and evolution of salted meat in Brazil and its quality parameters. The surveys analyzed to compose this systematic review were consulted in the following online databases: Scielo (Scientific Electronic Library Online), Periodico Capes, and Science Direct, using the following search terms: “Carnes Salgadas” “Carne de Charque”, “Carne de Sol”, “Qualidade da Carne”, “Microbiologia” e “Beef jerky”. The period defined for the inclusion of published research was delimited between the years 2010 to September 2021. Initial searches in online databases indicated a total of 637 works on the subject of salted meat, found using the words- key. By delimiting the production time between the years 2010 to 2021, we obtained a total of 136 related articles, which were published through their titles and abstracts, discovering a total of 32 articles found. To identify those who had a direct relationship with the central theme of this research, the methodologies were studied. Therefore, 17 articles were objectively and carefully selected to compose this systematic review. To characterize an analysis carried out in every bibliographic survey, whether under historical, technological, or gastronomic parameters, it is possible to visualize the historical and technological impact that this food has no progress in its development, in addition to verifying an advance in production techniques and quality of salted meats.